Synthesis, characterization and antibacterial activities of hydrazone schiff base compounds and its derivatives [Sintesis, pencirian dan aktiviti antibakteria sebatian bes schiff hidrazon dan terbitannya - Ruwaida Asyikin, Abu Talip; Meng, Guan Tay; Hashimatul Fatma, Hashim (Malaysian Society of Analytical Sciences, 2017)
Biological activities (e.g. antibacterial) of hydrazone compound have received much attention from the synthetic chemists since last two decades. Herein, we would like to report the synthesis pathways as well as the spectroscopic characterization of three etherified hydrazone Schiff base compound, which were initiated from 2-hydroxyacetophenone. Hydrazone Schiff base compound was obtained through condensation reaction between 2-hydroxyacetophenone with benzhydrazide. Meanwhile the etherified derivatives of hydrazone Schiff base were prepared via Williamson ether synthesis under reflux condition. All the synthesized compounds were characterized using Fourier transformation infrared, UV-Vis and 1H nuclear magnetic resonance spectroscopy. In addition, the antibacterial activities of these compounds were also conducted using disc diffusion method against Bacillus cereus and Escherichia coli.